Systematic design approach for a gain boosted telescopic OTA with cross‐coupled capacitor. Issue 3 (18th April 2017) - Joshi, Ashish; Shrimali, Hitesh; Sharma, Satinder K.
Abstract : A symbolic analysis is presented to study a gain‐boosted telescopic operational transconductance amplifier (OTA) with cross‐coupled capacitor (positive feedback) across an auxiliary op‐amp. The effects of positive feedback capacitor (PFC) on the pole–zero doublet introduced by the auxiliary op‐amp are explored using analytical techniques and simulations. A complete transfer function of the OTA with PFC across the auxiliary op‐amp is derived and verified through circuit simulations. The results obtained from circuit simulation and modelled transfer function show good agreement with each other. Furthermore, the analytical expressions for the feedback capacitor in terms of pole–zero locations, unity gain bandwidth (UGBW) and phase margin (PM) are presented. It is shown that UGBW, PM and settling behaviour of the OTA can be tuned by the PFC. A systematic design approach to improve the PM and settling behaviour is discussed. On the basis of the theory presented, 17% improvement in 0.01% settling time is demonstrated.